Estudio para la implementación de reconectadores mediante aplicación de la ley de Pareto para determinar el 20% de las causas que generan el 80% de las fallas en el servicio eléctrico desde el km 5 hasta el km 24 en vía a la costa en Guayaquil, en media tensión de las redes de distribución. - Díaz Jordán, Jefferson Ricardo (2019)
This study will be carried out in order that in the future the electric company CNEL Guayaquil Business Unit can provide an efficient distribution of medium voltage energy to road users to the coast, located northwest of the city of Guayaquil. By means of a statistical study, it is also intended to reduce the different types of failures that exist in feeder operations in previous years, trying to identify the critical points in order to determine the possible solutions. By creating surveys and statistical data it is possible to determine specific places through a Pareto Law table of 80-20%, which will help, to take solutions in strategic locations to obtain a more timely result. There are three substations in the path to the coast, in each substation there is an operator that determines by installed alarms any failure produced, the same ones that are reported to the SCADA Central, which generates actions to be executed and possible tests depending on type of localized fault of the place, to be able to install in strategic points recloses that are going to help to have an efficient quality of energy, where it is tried to reduce the time of response of attention for the repair and determination of failures, some of them in certain circumstances could be of complex solution, and in special cases can postpone days in the repair since there could be no availability of materials or climatic conditions that affect the distribution networks. With recloses it´s expected to solve drastic impacts in the distribution network, which affect the flow of energy to its destination. Selection of the reclose type will be determined based on the vacuum, quality, response time and security tests that will be provided when installing it.